THE EFFECT OF THE NUMBER OF TOURISM ATTRACTIONS AND RESTAURANTS ON LOCAL OWN-SOURCE REVENUE IN THE REGENCY/CITY OF LAMPUNG PROVINCE - Aminda, Renea Shinta; Rahmawati, Evi (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2023)
Local own-source revenue has an important role in supporting local government funding sources to finance all regional operational and development needs, and other forms of public services. Therefore, to increase local revenue, the government must optimize which sectors can contribute. One of the efforts to increase local own source revenue is by optimizing the potential in the tourism sector. The tourism sector will contribute to local own source revenue through tourist attraction fees and restaurant taxes. This research was conducted to determine the effect of the number of tourist attractions and restaurants on Local Own –Source Revenue in the Regency/City of Lampung Province in 2011-2020. The data in this study is secondary data obtained through the Central Bureau Statistics and the Lampung Provincial Tourism Office. This study uses panel data regression analysis with the program used, namely Stata14, and uses hypothesis testing on a significance basis of 0.05 or 5%. The results of this study indicate that (1) tourist attractions do not have a significant influence on Regional Original Income in Lampung Province (2) restaurants have a significant influence on Local Own-Source Revenue in the Regency/City of Lampung Province. In addition, from this study, it can be seen that the variable number of tourist visits and restaurants has an effect on Local source revenue. The data in this study is secondary data obtained through the Central Bureau Statictic (BPS) and the Lampung Provincial Tourism Office. This research is a type of quantitative descriptive research with an analysis method using panel data regression with the program used, namely Stata 14, and uses hypothesis testing on a significance basis of 0.05 or 5%. The results of the tests conducted in this study are that there is no significant effect where when tourist attractions increase it does not result in an increase in Local Own – Source Revenue. Restaurants have a significant influence on Local Own – Source Revenue in the Regency/City of Lampung Province in 2011 and 2020. This shows that restaurants are one of the indicators of increasing Local own-source Revenue in the Regency/City of Lampung Province